The growth of 'Crystal' guava seedling in response to pinching and dormancy breaking chemicals - Raden Ajeng Diana Widyastuti; Setyo Dwi Utomo; Darwin H. Pangaribuan; Purba Sanjaya; Hayane Adeline Warganegara; Widia Agustin (Kultivasi, 2022)
AbstractPinching and dormancy breaking chemicals (DBC) application are potentially used to regulate the growth of plant. This study aims to evaluate the growth response of ‘Crystal’ guava (Psidium guajava L.) seedling in response to pinching and DBC application. This experiment was carried out in the Integrated Field Laboratory, Faculty of Agriculture, Universitas Lampung from March to June 2021, with a randomized completely block design (RCBD) with 2 factors (pinching and DBC) and repeated four times. The results showed that pinching could reduce the increase of height of guava seedling. The combination of pinching with DBC could significantly increase the number of new emerging leaves, branches, and shoots as well as the length of new shoots. The leaf area on new emerging leaves was not affected by pinching and DBC factors. The application of DBC to non-pinched plants inhibited vegetative growth and precisely increased generative growth, as indicated by the increase of the number of flowers produced. The most recommended treatment to improve the vegetative growth of guava plant seedlings was a combination of pinching and KNO3 40 g L-1.Keywords: 'Crystal' guava, KNO3, vegetative growth, pinching, dormancy breaking chemicals. AbstrakPinching dan pemberian zat pemecah dormansi berpotensi untuk digunakan sebagai pengatur pertumbuhan tanaman. Penelitian ini bertujuan untuk mengevalusi respon pertumbuhan bibit tanaman jambu biji (Psidium guajava L.) 'Kristal' terhadap perlakuan pinching dan pemberian zat pemecah dormansi (ZPD). Percobaan ini dilaksanakan di lahan Laboratorium Lapang Terpadu, Fakultas Pertanian, Universitas Lampung dari bulan Maret hingga Juni 2021, dengan rancangan acak kelompok (RAK) faktorial (pinching dan ZPD) yang diulang sebanyak 4 kali. Hasil penelitian ini menunjukan bahwa teknik pinching dapat menurunkan pertambahan tinggi tanaman jambu. Namun hal ini justru dapat memperbaiki pertumbuhan bibit jambu. Kombinasi pinching dengan ZPD dapat meningkatkan jumlah daun, cabang, dan tunas baru serta panjang tunas baru secara signifikan. Luas daun baru tanaman jambu tidak dipengaruhi oleh faktor pinching dan ZPD. Pemberian ZPD pada tanaman yang tidak dipinching menghambat pertumbuhan vegetatif, sebaliknya meningkatkan pertumbuhaan generatif dengan indikator peningkatan jumlah bunga yang diproduksi. Perlakuan yang paling direkomendasikan untuk memperbaiki pertumbuhan vegetatif bibit tanaman jambu adalah kombinasi antara pinching dan KNO3 40 g L-1.Kata kunci: jambu biji ‘Kristal’, KNO3, pertumbuhan vegetatif, pinching, zat pemecah dormansi